A Historical Perspective on Land Tenure Security - Sunderlin, W.D.; Holland, M.B. (Springer, 2022)
In this chapter, we explore the forces that have shaped the current challenge of securing land tenure for those with little voice, power, and means. Focusing on the Global South, we identify trends in the ebb and flow of land tenure security and insecurity, distinguishing between those tied to agricultural-based societies and forest-dependent populations where relevant. We spotlight the broad arc of history tied to land access: the widespread acquisition of land by the powerful dating several centuries back, the partial restoration of local land access beginning in the mid-twentieth century (e.g., post-colonial governments, agricultural land reform and redistribution movements, and forest management devolution), the land-grabbing phenomenon and violence of recent years, and the current uncertainty over future directions for tenure security.